1996
DOI: 10.1103/physrevlett.77.3979
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Dynamics Studied by Polarization Modulation

Abstract: We observed and made unambiguous distinctions between abrupt photophysical events of single molecules: a rotational jump of a single dipole, a transition to a dark state (reversible and irreversible photobleaching), and a spectral jump. The study was performed in the far field by modulating the excitation polarization and monitoring the fluorescence in time. This technique also allowed us to measure the in-plane dipole orientation of stationary single molecular dipoles with subdegree accuracy and to resolve de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
335
1
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(347 citation statements)
references
References 16 publications
5
335
1
4
Order By: Relevance
“…Figure 5 shows a sequence of images of a blinking single GFP. Similar but less frequent blinking behavior has also been seen for some but not all single choromophores (42). A general strategy to distinguish photoinduced and spontaneous processes is to check the excitation intensity dependence.…”
Section: Photophysics and Photochemistry In Single-molecule Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows a sequence of images of a blinking single GFP. Similar but less frequent blinking behavior has also been seen for some but not all single choromophores (42). A general strategy to distinguish photoinduced and spontaneous processes is to check the excitation intensity dependence.…”
Section: Photophysics and Photochemistry In Single-molecule Measurementsmentioning
confidence: 99%
“…Similarly, the emission intensities of single molecules fluctuate as the result of the spectral changes (17,42). These intrinsic fluctuations contain rich dynamic information of single molecules and their interacting environments.…”
Section: Spectral Fluctuationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, immobile fluorescing SMs produce an inherently anisotropic emission pattern that depends on the orientation of the SM emission dipole moment relative to the optical axis (7,8). The work by Enderlein et al (9) has shown that fitting such an SM image to a 2D Gaussian can result in position errors of tens of nanometers for molecules located in the microscope's focal plane.…”
mentioning
confidence: 99%
“…Individual behaviors can be assessed by single-fluorophore imaging (1)(2)(3)(4)(5), which is much less perturbing than imaging through a huge tag such as a plastic bead or actin filament (6). Real-time determination of fluorophore orientation (5,7,8) should be particularly useful, because a conformational change necessarily accompanies reorientation of one part against others. Thus far, however, successful applications of this potentially powerful method have been made infrequently.…”
mentioning
confidence: 99%